Activation of Bovine Factor X in the Presence of Calcium, Magnesium, Barium or Manganese ion - Yue, Robert H; Gertler, Menard M (Thrombosis and Haemostasis, 1978)
The binding of divalent metal ions to bovine factor X, factor Xa and the coagulant protein in Russell’s viper venom was studied by the technique of fluorescence quenching. Titration of factor X with Ca+2, Mg+2 or Ba+2 revealed that these metal ions can bind to factor X. A tightly binding site(s) was observed with Kd of 79 and 98 μM for Ca+2 and Mg+2 respectively. A loosely binding site(s) was evident with Kd of 0.55, 0.50 and 0.35 mM for Ca+2, Mg+2 and Ba+2 respectively. The quenching phenomenon was also observed when Mn+2 was used as titrant but factor X precipitated out when the concentration of Mn+2 was 10 mM. The binding of Ca+2, Mg+2, Ba+2 or Mn+2 to bovine factor Xa or to the purified coagulant fraction of Russell’s viper venom was very weak in each case.In the absence of Ca+2, the coagulation fraction of Russell’s viper venom could not activate bovine factor X. Activation of factor X was achieved when Ca+2 was replaced by either Mg+2, Ba+2 or Mn+2. When the concentration of these ions were 5 mM, the efficiency of factor Xa generation was estimated to be: Ca+2> Mg+2> Ba+2> Mn+2. Higher concentration of Mg+2, Ba+2, or Mn+2 retarded the activation process. However, Ca+2, Mg+2, Ba+2 or Mn+2 has little or no influence on the esterase activity of factor Xa or purified Rusell’s viper venom.The results suggest that complexation of divalent metal ion with factor X is prerequisite in the activation process. The binding of Mg+2, Ba+2 or Mn+2 to these loosely binding sites might have altered the geometrical configuration as well as the electrostatic environment on factor X significantly. Thus, it is more difficult to form the binary complex and a slower generation of factor Xa results. Therefore, divalent metal ion serves as a dual role in the activation of factor X to factor Xa depending upon the ionic concentration.